2021
DOI: 10.1016/j.jaci.2020.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroids downregulate the SARS-CoV-2 receptor ACE2 in COPD through suppression of type I interferon

Abstract: Background The mechanisms underlying altered susceptibility and propensity to severe Coronavirus disease 2019 (COVID-19) disease in at-risk groups such as patients with chronic obstructive pulmonary disease (COPD) are poorly understood. Inhaled corticosteroids (ICS) are widely used in COPD but the extent to which these therapies protect or expose patients to risk of severe COVID-19 is unknown. Objective The aim of this study was to evaluate the effect of ICS upon pulmon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 45 publications
(70 reference statements)
4
98
1
Order By: Relevance
“…Researchers have reported that the prevalence of asthma and COPD among hospitalised COVID-19 patients may be lower than in the general population 22 and recent research by Finney et al 23 has demonstrated using human and animal in vitro and in vivo disease models that inhaled corticosteroid (ICS) administration attenuates pulmonary expression of the SARS-CoV2 viral entry receptor angiotensin-converting enzyme (ACE)-2 which it is postulated may result in reduced susceptibility to COVID-19 infection. Systemic steroids may also mediate suppression of IFN and attenuate ACE2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have reported that the prevalence of asthma and COPD among hospitalised COVID-19 patients may be lower than in the general population 22 and recent research by Finney et al 23 has demonstrated using human and animal in vitro and in vivo disease models that inhaled corticosteroid (ICS) administration attenuates pulmonary expression of the SARS-CoV2 viral entry receptor angiotensin-converting enzyme (ACE)-2 which it is postulated may result in reduced susceptibility to COVID-19 infection. Systemic steroids may also mediate suppression of IFN and attenuate ACE2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The corticosteroid ciclesonide also appears to attenuate SARS-CoV-2 replication in vitro by targeting non-structural protein 15, an endoribonuclease which helps evade host detection of viral double-stranded RNA and type 1 IFN responses [ 89 91 ]. ICS may also prevent SARS-CoV-2 entry; ACE2 gene expression is lower in the sputum of COPD and asthma patients who use ICS compared to those who do not [ 92 , 93 ]. Furthermore, studies in mice have shown that ICS reduce ACE2 expression by inhibiting type 1 IFN production [ 92 ].…”
Section: Ics Use In Copd: Implications For Covid-19mentioning
confidence: 99%
“…ICS may also prevent SARS-CoV-2 entry; ACE2 gene expression is lower in the sputum of COPD and asthma patients who use ICS compared to those who do not [ 92 , 93 ]. Furthermore, studies in mice have shown that ICS reduce ACE2 expression by inhibiting type 1 IFN production [ 92 ]. While suppression of type 1 IFN secretion may reduce host defence, the associated reduction of ACE2 expression may protect against SARS-CoV-2 cellular entry.…”
Section: Ics Use In Copd: Implications For Covid-19mentioning
confidence: 99%
“…168 In vitro, a combination of glycopyrronium, formoterol, and budesonide appeared to inhibit viral replication in infected nasal and tracheal epithelial cells 169 and ACE2 expression was found to be decreased in sputum cells of asthmatic and COPD patients on ICS. 163,170 Questions have also been raised regarding the effect of type 2 biologic therapy on COVID-19 infectivity and outcomes. Observational experiences reported to date do not provide evidence that type 2 biologics are associated with increased risk for COVID-19 infection or higher COVID-19 disease severity.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“… 168 In vitro, a combination of glycopyrronium, formoterol, and budesonide appeared to inhibit viral replication in infected nasal and tracheal epithelial cells 169 and ACE2 expression was found to be decreased in sputum cells of asthmatic and COPD patients on ICS. 163 , 170 …”
Section: Introductionmentioning
confidence: 99%